PENGEMBANGAN MEDIA FILM KARTUN BERBAHASA JAWA UNTUK PEMBELAJARAN BERDIALOG SISWA KELAS X SMA DI BANYUMAS - Witriningrum, Sri Galuh; Kurniati, Endang; Sukoyo, Joko (Jurnal Penelitian Pendidikan, 2017)
This purpose of this research aims to develop the media dialouge using wangsalan/parikan by utilizing the Javanese cartoon move as the mdia in accordance with Javanese manners. The study design is Research and Development (R&D). The research used questionnaire of teacher and action test. The analysis of data is using qualitative descriptive analysis. The result of dvelopment Javanese cartoon movie as a media is adequate, effective, and material has also been good.